Instrumen Penilaian untuk Pembelajaran Ekologi Berorientasi Literasi Saintifik - Setiawan, Adib Rifqi (Department of Biology Education, Universitas Pendidikan Indonesia, 2019)
The aims of this cross-sectional survey research was to find the validity and reliability of assessment instruments for ecological learning scientific literacy oriented’s. Determination of the sample used purposive sampling of 4 experts and 122 high school level students. To reveal validity is assessed based on obtain judgment expert and reliability measured by internal consistency. It was gained that the validity is 7 items very feasible and 3 item quite feasible with reliability’s value is 0.763. It showed that all items can be used to analyzing the difficulties of students for designing ecological learning scientific literacy oriented’s lesson plans.